أثر العوامل البيئية على التوجه المقاولاتي النسوي دراسة حالة النساء المقاولات بولاية الأغواط - بن مسعود سارة; عبو فاطمة; نعيجات عبد الحميد (جامعة عمار ثليجي الاغواط, 2022)
Our study aims to learn about the impact of environmental factors on women's orientation towards entrepreneurship. The study was conducted with a sample of women contractors in the state and municipalities of Laghouat, where we relied on a study model of an independent variable of environmental factors: Pioneering education (Entrepreneurship), unemployment, socialization, Internet and government support, and a dependent variable of feminist entrepreneurial orientation, to achieve the objectives of the study, we used the questionnaire tool, which was distributed to 93 individuals, and to analyze the data based on Spss and Smart-Pls to study the different relationships between the studied variables. The results of the study were a statistically significant effect at the 5% morale level of environmental factors on women's entrepreneurial orientation. The study concluded with recommendations that could contribute to the dissemination of women's entrepreneurship culture and raise awareness of it such as focusing on entrepreneurial education and giving it greater importance by intensifying meetings, seminars, and training courses on entrepreneurship and disseminating entrepreneurial culture as well as a review of the State's support for young people, especially the feminist component, To provide more appropriate Islamic funding formats and facilities, the media must focus on spreading the culture of entrepreneurship in order to change society's perception of women entrepreneurs.